Participation of older people in recreation movement anda sense of quality of life - Gumola, Katarzyna (Biospołeczne uwarunkowania uczestnictwa w kulturze fizycznej i zdrowotnej osób w różnym wieku, 2017)
An analysis concerns the level of the sense of quality of life among the people 60+. There has been shown the evaluation of sense of satisfaction with life on a global scale and in selected areas of quality of life among older people not participating in physical recreation at all and four weeks after taking up physical recreation. Test results: The vast majority of respondents after the participation in recreation is happy with their physical shape, contact with friends, relationships with family and peace of mind. Adoption of physical activity impact on the perception of the ability to perform the duties of everyday life and consciousness of energy level and the will to manage their own lives, including leisure activities according to their own tastes. Conclusion of the study: Promotion of various forms of physical activities among the elderly can contribute to improvement of their quality of life.